Networks and the duration of temporary migration - Ira N. Gang; Thomas Bauer (Rutgers University, Department of Economics, 2002)
This paper analyzes the determinants and timing of return migration. Special attention is paid to the role of social and informational migration networks. A simple theoretical model of temporary migration demonstrates that the effect of migration networks on optimal migration duration is ambiguous. We investigate the determinants of migration duration using a semiparametric proportional hazard model for discrete duration data. Our data consists of a sample of return migrants from six villages in Egypt. Controlling for human capital and demographic characteristics of the migrants and economic indicators of the host country, the estimation results show that social and informational networks have a statistically significant negative effect on migration duration.
Keywords: J61; 330; duration of migration; Egypt; return migration; temporary migration